Guidelines for Da'wah Bilhikmah of the Indonesian Ulema Council in Dealing with Hoaxes on Social Media - Nashrillah Nashrillah; Datuk Imam Marzuki (Budapest International Research and Critics University, 2021)
Da'wah bilhikmah is a message that is able to guide people in tracing the traces of the glory of life and high civilization, so that humans become dignified (akramal akramin). The description of the da'wah bilhikmah in the Qur’an can be carried out by preachers / preachers who have wisdom, namely those who are called ulil ilmi and ulil albab who are always devoted (reflecting), tafakkur (deep thinking), polite in attitude ( hilm), fair in deciding and progressive in truth (I'tiba). In this research, the writer tries to get library material, namely collecting, reading and reviewing sources, getting library research in the form of books or the realities of everyday life of the people related to the issues discussed. The method of discussion in this research are: Synthesis Analysis Method, namely through rational and abstract logical approaches to the objective of inductive and deductive thinking and scientific analysis. Descriptive method, namely by describing the ongoing and developing social reality which is then associated with the issue of da'wah and its scope. In writing this journal, sociology theory states that humans develop religion (religion) because of the vibrations of the soul and religious emotions that arise due to the influence of social feelings. Namely by describing the ongoing and developing social reality which is then associated with the issue of da'wah and its scope. In writing this journal, sociological theory states that humans develop religion (religion) because of the vibrations of the soul and religious emotions that arise due to the influence of social feelings. Namely by describing the ongoing and developing social reality which is then associated with the issue of da'wah and its scope. In writing this journal, sociology theory states that humans develop religion (religion) because of the vibrations of the soul and religious emotions that arise due to the influence of social feelings.